2016
DOI: 10.1016/j.jaci.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

A work group report on ultrafine particles (American Academy of Allergy, Asthma & Immunology): Why ambient ultrafine and engineered nanoparticles should receive special attention for possible adverse health outcomes in human subjects

Abstract: Ultrafine particles are airborne particulates of less than 100 nm in aerodynamic diameter. Examples of ultrafine particles are diesel exhaust particles, products of cooking, heating and wood burning in indoor environments, and more recently, products generated through the use of nanotechnology. Studies have shown that ambient ultrafine particles have detrimental effects on both the cardiovascular and respiratory systems, including a higher incidence of atherosclerosis and the exacerbation rate of asthma. Ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 126 publications
5
136
1
3
Order By: Relevance
“…SSDs not already published in the literature are presented in Figure S21. 143 Models are always simplifications developed for specific objectives. In this case, the objective was to evaluate the largescale regional fate of specific ENMs and provide a rapidscreening tool.…”
Section: Significancementioning
confidence: 99%
“…SSDs not already published in the literature are presented in Figure S21. 143 Models are always simplifications developed for specific objectives. In this case, the objective was to evaluate the largescale regional fate of specific ENMs and provide a rapidscreening tool.…”
Section: Significancementioning
confidence: 99%
“…Nanoparticles (NPs) with their varied physicochemical properties, elicit a wide range of physiological responses such as distribution patterns and interactions with biological molecules . Although, particle size and surface area of the particles are important features that affect in vivo bio reactivity, crystal structure, purity, hydrodynamic size, and aggregation nature of the NPs in aqueous media also regulate the biological response .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that particle exposures have resulted in the respiratory inflammation response [18], alveolar enlargement [19], oxidative stress [20], and alveolar lavage fluids [21]. The allergy response was the most reported cases [22], [23]. The other circumstances were influenza-like illness [24], alveolar emphysema [25], lung cancer [26], and chronic obstructive pulmonary disease (COPD) [27].…”
Section: Introductionmentioning
confidence: 99%